Interactive Whiteboards in Higher Education: Instructors First Impressions - Demirli, Cihad; Turel, Yalin Kilic (Ani Yayincilik, 2012)
Problem Statement: Recently, in the context of the technology integration in school settings, the importance and the portion of interactive whiteboard (IWB) use have been increased gradually in all over the world. As the costs of IWBs have declined and their features have been improved, the availability of IWBs in schools has become pervasive. This situation arises several questions such as how instructors effectively use IWB in their classrooms and how the potential and effective use of IWBs can be improved. For relatively a new technology being used by instructors in schools, the perceptions and perspectives of instructors are considered essential to answer such questions. Purpose of the study: Most research studies indicate that IWBs have potential to facilitate instruction and also have positive effects on students' learning and motivation in general, when they are used appropriately in instruction. In other studies, teachers' perspectives were also examined in terms of a variety of dimensions of IWB use including teachers' attitudes, competencies, necessities, knowledge, and skills regarding IWB use by means of various methods and tools. However, there are few studies mainly focusing on IWB use in higher education. In this study, believing in the importance of the first impression and opinions of teachers, as main users of IWB technology, we aimed to focus on instructors' views and suggestions to make IWBs more productive and effective instructional tools in higher education classrooms. We think that based on the instructors' first impressions and suggestions, instructors and administrators in higher education as well as researchers who are interested in the use of IWB in education may develop new and effective strategies regarding IWB use and also evaluate the effects of IWB on learning and instruction in higher education. Method: In total, 39 instructors were participated. They were provided eight-hour IWB orientation, a CD that includes information about IWB use, strategies and techniques for IWB use, and the essential parts of the recorded face-to-face IWB training session. The instructional materials were designed to cover what each instructor (faculty member) would have taught in 9th and 10th week of the semester. Then, instructors piloted the materials with the support of assigned instructional designers. At the end of this implementation, teachers filled up an online questionnaire which consists of teachers' demographic information as well as their perceptions and impressions about the IWB use. Teachers also asked to clearly reflect their perceptions about the positive and negative aspects of the IWB via open-ended questions. Descriptive analysis (i.e., frequencies and percentages) were used for the presentation of the quantitative data. In addition, we have performed the content analysis via QSR Nvivo 8 for teachers' comments to open-ended questions. Findings: Regarding the main findings of this study, we can conclude that instructors develop positive attitude about IWB use. Almost all instructors had strongly positive attitudes towards the use of that technology after the implementation. Particularly for instructors who were in the second decade of their professions, their perceptions can be regarded as more valuable. Only few instructors were undecided on using an IWB while others were planning to use it in their future courses. Another satisfactory finding is that instructors did not have any negative experiences in terms of classroom management during their IWB use. Furthermore, they expressed that they enjoyed during the implementation process and also observed similar reactions from their students while IWBs were being used. In addition, instructors stated that IWBs were more suitable for courses like Science and Mathematics rather than Language and Social Studies. Despite all positive aspects of IWB use, instructors highlighted some technical issues and a need for re-organizing physical conditions of classroom settings as prominent problems that are to be solved for the success of IWB use. Conclusion: This study raised critical issues in terms of IWBs use in classroom settings. First of all, instructors stated that Science, Mathematics and similar courses can be taught with IWBs support. However, IWBs can be used in various contexts and with various instructional methods and techniques. There are many functional tools in the IWB software that comes with the IWB package for a wide range of course content such as Music and Social Sciences. It is clear that instructors' awareness regarding the existence of these tools was insufficient. Future research is needed to examine the reasons behind their selections of courses in which IWB could be used effectively. In addition, instructors thought that IWB could be used with a variety of instructional methods and techniques and this idea provides a basis for the notion of using IWBs in various types of courses. In general, these findings reveal a better understanding of usability of IWBs for instructors who are from different fields and are planning to use IWBs in their courses. Another remarkable advantage of IWB use is that this technology helps instructors present their course content in more interactive, enjoyable, and visual ways. Despite all positive aspects of IWB use, there are still some problems requiring solutions for an optimum instruction. Need for better physical conditions of classroom settings and technical support are the prominent issues arising from TWB use. Thus, in order to provide an effective use of this technology, classroom settings need to be re-designed based on the basic requirements of the technology use (i.e., appropriate illumination of classroom, sitting plan, position of the projector and the IWB). In addition, teachers should be provided a solid technical support both before and during the instruction. In that way, instructors could merely focus on the use of technology instead of giving their time to arrange physical conditions or overcome technical issues.
Keywords: Interactive whiteboard; instructors' perceptions; higher education; technology integration